Origin of Multisynaptic Corticospinal Pathway to Forelimb Segments in Macaques and Its Reorganization After Spinal Cord Injury - Ninomiya, Taihei; Nakagawa, Hiroshi; Inoue, Ken-ichi; Nishimura, Yukio; Oishi, Takao; Yamashita, Toshihide; Takada, Masahiko (Frontiers in Neural Circuits, 2022)
Removal of the monosynaptic corticospinal pathway (CSP) terminating within the forelimb segments severely impairs manual dexterity. Functional recovery from the monosynaptic CSP lesion can be achieved through the remaining multisynaptic CSP towards the forelimb segments. In the present study, we applied retrograde transsynaptic labeling with rabies virus to a monkey model of spinal cord injury. By injecting the virus into the spinal forelimb segments immediately after the monosynaptic CSP lesion, we showed that the contralateral primary motor cortex (M1), especially its caudal and bank region (so-called “new” M1), was the principal origin of the CSP linking the motor cortex to the spinal forelimb segments disynaptically (disynaptic CSP). This forms a striking contrast to the architecture of the monosynaptic CSP that involves extensively other motor-related areas, together with M1. Next, the rabies injections were made at the recovery period of three months after the monosynaptic CSP lesion. The second-order labeled neurons were located in the ipsilateral as well as in the contralateral “new” M1. This indicates that the disynaptic CSP input from the ipsilateral “new” M1 is recruited during the motor recovery from the monosynaptic CSP lesion. Our results suggest that the disynaptic CSP is reorganized to connect the ipsilateral “new” M1 to the forelimb motoneurons for functional compensation after the monosynaptic CSP lesion.